Oxford Handbooks Online 2018
DOI: 10.1093/oxfordhb/9780190279707.013.10
|View full text |Cite
|
Sign up to set email alerts
|

Testing Theories of Social Disorganization in Nigeria

Abstract: This chapter focuses on the social disorganization approach to understanding variations in area-level rates of crime. It first provides context through a brief description of the study area, Badarawa-Malali, an urban district in the city of Kaduna, Nigeria (Section 17.2). Section 17.3 provides a review of the different components of social disorganization theory, the mechanisms through which they are believed to operate, how they have been estimated in previous studies, and whether they are meaningful in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In this study, it is observed that crimes tend to concentrate in the urban centres. This was consistent with what was already known generally about the geographic distribution of crime in metropolitan areas [43,44] .…”
Section: Crime Hotspots In Northern Tarabasupporting
confidence: 92%
“…In this study, it is observed that crimes tend to concentrate in the urban centres. This was consistent with what was already known generally about the geographic distribution of crime in metropolitan areas [43,44] .…”
Section: Crime Hotspots In Northern Tarabasupporting
confidence: 92%
“…Limited access to quality education and employment opportunities can result in a sense of alienation and disconnection among residents. This breakdown of social networks and community structures may create an environment where criminal behavior becomes more prevalent (Umar, Johnson & Cheshire, 2018;Akinwale & Aderinto, 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 99%